Canine oral fibrosarcomas: a retrospective analysis of 65 cases (1998–2010)1. (18th February 2013) - Gardner, H.; Fidel, J.; Haldorson, G.; Dernell, W.; Wheeler, B.
Abstract The objective of this retrospective study was to report the outcome of treatment of canine oral fibrosarcomas (FSA) in relation to median survival and progression‐free survival (PFS), and to report whether grade was prognostic in relation to median survival. Sixty‐five dogs with oral FSA presented to the WSU VTH between June 1998 and March 2010. Significant predictors of median survival were location (P = 0.0099), tumour size or oral stage (P = 0.0312), type of surgery (P = 0.0182), margins (P = 0.0329) and grade (P = 0.0251). Significant predictors of PFS were location (P = 0.0177), and radiation protocol (P = 0.0343). A combination of surgery and radiation was the strongest predictor of prolonged median survival (P = 0.0183) and PFS (P = 0.0263) at 505 and 301 days, respectively. Treatment of canine oral FSA with a combination of surgery and radiation therapy provided the longest median survivals.